Can femme be theory? Exploring the epistemological and methodological possibilities of femme. Issue 1 (2nd January 2021) - Hoskin, Rhea Ashley
Abstract: Narrative-works are the lifeblood of femme scholarship. Through this medium, femmes write themselves into existence. In this article, I begin with my own story of femme and examine the backdrop of patriarchal femininity that positions pieces of me as being at odds, disjointed, and something needing to be reconciled. Indeed, many current frameworks and dominant framings for understanding femininity create disjunctures needing to be reconciled and fail to include diverse feminine perspectives in ways that constitute epistemic and hermeneutical injustices. Using my own femme becoming as a guide, I offer this process of femme reconcilement as a framework that can be applied to dislodge feminine normativity and challenge the assumptions researchers make about femininity within their work. In this article I highlight the importance of femme epistemologies; the importance of valuing feminine knowledge, and how the absented femme highlights the continued god-trick of objectivity. Here, I discuss how femme narratives can be used to bolster femme as theory and critical analytic. This situated knowledge holds the possibility to inform novel methodological frameworks and to substantially shift the way researchers think about femininity and feminine people.